Westminster Traditions: Continuity and Change. Issue 4 (25th July 2016) - Weller, Patrick; Haddon, Catherine
Abstract : This article analyzes what the Westminster system actually means for civil services in historical context and contemporary practice. It explores the way in which practitioners, both politicians and civil servants, interpreted Westminster's implications and used them as justification, defense, and sometimes camouflage for their administrative choices in a range of jurisdictions. The article then uses the example of senior appointments to show why these nuanced interpretations are significant. Its principal finding is that the continued value of Westminster lies in its ability to provide a framework and discourse without being prescriptive or precise for particular circumstances. It is sufficiently flexible to be able to evolve with the needs of each generation yet continues to frame a sense of identity and purpose in how it is applied in abstract and practice.